(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the translation challenges of sewing terminology in English and Uzbek. Terminology used in the sewing industry evolves alongside technological developments and is influenced by cultural differences and language-specific features, which create difficulties in translation. In the process of translating English sewing terms into Uzbek, challenges arise due to the lack of direct equivalents, cultural differences, and the complexity of technical concepts. The article discusses various approaches to addressing these challenges, including descriptive translation, the use of context, and the borrowing of foreign terms.